Telaah Literatur tentang Perilaku Seks Bebas pada Remaja sebagai Manifestasi Perilaku Bermasalah - Graciella Lumban Gaol; Raul Rian Shaputra; Risma Anita Puriani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to analyze promiscuous sexual behavior among adolescents as a manifestation of problematic behavior through a literature review approach. The method used was a literature review with a descriptive-analytical design, analyzing 20 national scientific articles published between 2007 and 2024. The analysis process was conducted systematically through the stages of identifying relevant sources, classifying themes, extracting important data, and synthesizing findings to build a comprehensive conceptual framework. The study results were then grouped into four main aspects: internal factors, external factors, impacts, and prevention strategies. The study results indicate that promiscuous sexual behavior among adolescents is influenced by internal factors such as knowledge, attitudes, and moral reasoning, as well as external factors such as family environment, peers, social media, and lack of parental supervision. The resulting impacts are multidimensional, encompassing health (sexually transmitted infections and unplanned pregnancies), psychological (anxiety, guilt), and social (stigma and educational disruption). Effective prevention efforts involve comprehensive sex education, active family involvement, and collaboration between schools and the community.